The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/s0263574720001514
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experiments of Pneumatic Soft Actuators

Abstract: SUMMARY The soft actuator is made of superelastic material and embedded flexible material. In this paper, a kind of soft tube was designed and used to assemble two kinds of pneumatic soft actuators. The experiment and finite element analysis are used to comprehensively analyze and describe the bending, elongation, and torsion deformation of the soft actuator. The results show that the two soft actuators have the best actuation performance when the inner diameter of the soft tube is 4 mm. In addition, when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…At the maximum pressure of 1.8 bar, the average maximum elongation and contraction are 39.9% and 27.4%, respectively. The selfsensing IPAM performances are comparable with previous extensible pneumatic muscles (such as [27]), in terms of stroke. In addition, we observed that, upon pressurization, the actuator elongates and slightly rotates, because of the helical arrangement of the reinforcing structure [28].…”
Section: B Electro-mechanical Characterization Of the Ipamsupporting
confidence: 63%
“…At the maximum pressure of 1.8 bar, the average maximum elongation and contraction are 39.9% and 27.4%, respectively. The selfsensing IPAM performances are comparable with previous extensible pneumatic muscles (such as [27]), in terms of stroke. In addition, we observed that, upon pressurization, the actuator elongates and slightly rotates, because of the helical arrangement of the reinforcing structure [28].…”
Section: B Electro-mechanical Characterization Of the Ipamsupporting
confidence: 63%
“…Typical actuators based on pneu-nets are composed of two fundamental parts: an active top (characterized by a series of elastomeric chambers lined up in a row and linked up by a network of air channels) and a passive bottom (a strain-limiting layer which serves to curtail the extension of the active part) [21,32,33]. On the supply of pressure to the actuator, the chambers expand (significantly across the length) and cause the whole structure to bend in the longitudinal direction only.…”
Section: Actuator Designmentioning
confidence: 99%
“…However, when more motions are necessary, this method becomes unpractical due to the complexity of joining more than two actuators. Multiple motions soft actuators have been proposed [19][20][21][22][23][24] considering chambers or at least three independent channels, distributed homogeneously in the body, resulting in motions of elongation and multiple bending and performing deformations from 36 • to less than 160 • [19,[21][22][23][24][25][26] (depending on the angle measurement method). The motion variation depends on the method of measurement, manufacturing material and actuator geometry.…”
Section: Introductionmentioning
confidence: 99%